Recession and solution to recover hibah of Tabung Haji / Nurhazira Ahmad - Ahmad, Nurhazira (2019)
Tabung Haji (TH) is a short synonym for Lembaga Urusan dan Tabung Haji Malaysia (The Pilgrims Management and Fund Board of Malaysia) started its operation in 1963 to assist the Muslim/rural community in Malaysia with the financial costs of performing the hajj to Saudi Arabia. TH acts as an institution of savings for Muslims to fulfill their religious obligation. Lately, TH having financial problem which led to recession rate of hibah. TH as a role model of an Islamic financial institution for economic development has to give best looks as they represent as the only body to manage of hajj pilgrimage. This research attempts to highlight the reason of the recession and also provide a solution to giving back the hibah at the higher rate to depositors.